Cultivation and expansion of mesenchymal stem cells from human gingival tissue and periodontal ligament in different culture media - Banun Kusumawardani; Dwi Merry Christmarini Robin; Endah Puspitasari; Irma Josefina Savitri; Dea Ajeng Pravita Suendi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2021)
Background: Gingival tissue and periodontal ligament act as sources of mesenchymal stem cells (MSCs) that play a vital role in periodontal regeneration, but they both have limitations for cell availability. MSCs cultivated and expanded in various media formulations could be used as a basis for the development of cell therapy protocols. Purpose: This study aimed to determine the optimum culture media formulation for cultivation and expansion of human gingival-derived mesenchymal stem cells (hGMSCs) and human periodontal ligament stem cells (hPDLSCs). Methods: The hGMSCs and hPDLSCs were obtained from gingival tissue and periodontal ligament specimens from an adult patient. The two different culture media formulations used were: 1) α-minimum essential media (α-MEM) supplemented with 10% FBS, 100 U/mL penicillin, 100mg/mL streptomycin and 2.5 µg/mL amphotericin B; and 2) Dulbecco’s minimum essential media-Low Glucose (DMEM-LG) supplemented with 10% FBS, 2 mMol/L L-glutamine, 100 U/mL penicillin, 100mg/mL streptomycin and 2.5 µg/mL amphotericin B. The minced-gingival tissue and periodontal ligament samples were seeded in 3 cm tissue culture dishes with one of two experimental culture media, and incubated at 37oC in a humidified atmosphere of 5% CO2. Results: Cell morphology was observed on days two and five of the third passage. The gingival tissue and periodontal ligament primary cells exhibited fibroblast-like morphology, long processes and were spindle-shaped. The hPDLSCs grown in α-MEM exhibited a significant increase in cell viability and proliferation rate compared to the hPDLSCs grown in DMEM-LG. However, hGMSCs displayed similar cell viability and proliferation rate on both types of experimental media. Both the hGMSCs and hPDLSCs expressed MSC markers, including CD105, CD146, and CD90, but did not express CD45. Conclusion: Culture media formulations of α-MEM and DMEM-LG can be used for the cultivation and expansion of both hGMSCs and hPDLSCs.